Pengaruh Disiplin Kerja, Kompensasi, dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Sasana Antik Kabupaten Rembang - Ahmad Khoirul Anwar; Muhammad Tahwin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research explores how work discipline, compensation, and job satisfaction impact employee performance at PT Sasana Antik in Rembang Regency. The researchers used a sample of 62 employees and collected data through questionnaires. Multiple linear regression analysis was used to analyze the data. The results showed that work discipline has a positive but insignificant effect on employee performance, compensation has a significant positive effect on employee performance, and job satisfaction has a positive but insignificant effect on employee performance. The Adjusted R Square value shows that 19.9% of the variation in employee performance can be attributed to the three independent variables, while the remaining 80.1% can be explained by other factors not examined in this study.